PERAN LINGKUNGAN INTERNAL DAN FLEKSIBILITAS STRATEGI UNTUK MENINGKATKAN INOVASI USAHA MIKRO, KECIL DAN MENENGAH - Sumiati Sumiati (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Innovation is needed for every business organization, especially in the turbulence environments, as it is believed as a driver of business performance. This research aims to investigate the antecedents of innovation in Small and Medium Entreprises (SMEs) in Malang City. One hundred and eighty-seven questionnaires were collected by using purposive sampling technique. The data were analyzed by using partial least square. The hypothesis testing showed that all hypotheses are supported. Internal environment proven to be an antecedent of flexibility strategy and innovation. Furthermore, strategic flexibility is also proven as a driver of innovation. In addition, strategic flexibility also plays a mediating role in the relationship between internal environment and innovation. This research implies that in order to enhance SME’s innovativeness, the manager should ensure that the firm has a strong internal environment. A condusive internal environment will lead to the more flexible strategy and at the end it will enhance SME’S innovativeness. This research is projected to contribute to the body of knowledge, especially in the domain of strategic flexibility and innovation in SMEs in Indonesia. In addition, this research also gives guideline for SME manager about how to strengthen the innovation activities in their business organization